Uma análise dos impactos da Covid-19 no setor de transporte público urbano por ônibus - Lima, Aline de Araújo Celestino (2023)
The public transport sector is part of a service considered essential by the federal constitution of 1988 (CFB/88), as it corresponds to an indispensable service for citizens, since it provides the displacement of users to various places, such as work, study, leisure, fun, medical care, among many others. With the emergence of the new coronavirus in 2020, the actors of the transportation system (government, system operators and users) began to adopt measures so that the provision of the service would not be impaired with the impacts arising from the pandemic. However, in some locations of the country, strict measures such as social isolation were adopted, and directly impacted on the provision of business services, causing the suspension of the bus fleet in several municipalities in Brazil for 4 months, uncertainty for the financial and administrative health of the sector. Given this scenario, the present study aims to analyze the impacts suffered by the public transport sector by buses during the pandemic period, as well as the results from the measures of containment to the coronavirus, and the possible consequences that the pandemic can leave in the post-pandemic sector, contributing to the expansion of discussions from the perspective of all actors involved in the system, taking into account the theoretical framework. Thus, this study is based on the method of qualitative research, descriptive and exploratory, data was collected through bibliographical and documentary analysis using secondary data from the years 2020 to 2022 on the impacts caused by COVID-19 in the urban public transport sector by buses in Brazil.